Ways to Teach Students to Independent, Creative Thinking Through Practical Activities - Gulbahor Xamzayeva; Mukhtaram Rahimova (International Journal on Human-Computing Studies, 2021)
This article is about ways of teaching students to self – study, creative thinking through organizing practical lesson with innovative technologies at higher educational organization. This article describes the problem of increasing the self – activite of the assimilation of knowledge independent thinking by organizing self – education in higher educational institutions.